From Gujarat to global plates: An integrated assessment and meta-analysis of microplastics in commercially important pelagic fishes and human health risks - Jahnvi Oza; Krupal Patel; Jigneshkumar Trivedi (Marine Pollution Bulletin, 2026)

Tissue-specific distribution of microplastics in commercial crab Portunus segnis: a baseline data for sea-food security - Vasantkumar Rabari; Jigneshkumar Trivedi (Thalassas: An International Journal of Marine Sciences, 2026)

Spatial Ecology and Across-Shore Burrow Distribution of Ocypode rotundata Along the Kachchh Coast, Gujarat, India - Sebaj H. Gori; Pranav J. Pandya; Barathan Balaji Prasath; Krupal Patel; Jigneshkumar Trivedi; A. M. Elsawah; Deep D. Dudiya (Thalassas: An International Journal of Marine Sciences, 2026)

A new coral reef dromiid from Gujarat, India: Cryptodromia colini n. sp., with a note on the taxonomy of C. coronata Stimpson 1858 (Crustacea: Decapoda: Brachyura: Dromiidae) - Krupal Patel; Jigneshkumar Trivedi; Peter K. L. Ng (Marine Biology Research, 2026)

Molecular Phylogeny, Species Delimitation, and Biogeography of the Varunid Crab Genus Metaplax (Crustacea, Varunidae) - Jhih‐Wei Hsu; Hsi‐Te Shih; Mani Prema; Jigneshkumar Trivedi; Ngan Kee Ng; Min‐Yun Liu; Samuthirapandian Ravichandran; Peter K. L. Ng (Zoologica Scripta, 2026)
The Indo‐West Pacific genus Metaplax comprises 11 recognised species inhabiting intertidal mudflats, some adjacent to mangroves. To resolve long‐standing uncertainties, we analysed mitochondrial (COI, 16S) and nuclear (28S) markers. Phylogenetic analyses recovered Metaplax as monophyletic and resolved four well‐supported clades—the M. distincta , M. elegans , M. crenulata and M. indica clades—corroborated by morphology. COI barcoding delimited all 11 species, with intraspecific distances ≤ 2.01% and interspecific distances ≥ 5.76%, establishing a clear barcode gap. Molecular‐clock estimates date the split of Metaplax from other varunids to ca. 31.6 Ma, with subsequent diversification into four clades between 29.8 and 26.3 Ma. Ancestral‐range reconstructions support an Indian Ocean origin followed by stepwise dispersal into the western Pacific. These findings clarify interspecific relationships, confirm the utility of COI for Metaplax species delimitation, and suggest an Indian Ocean origin with later west‐to‐east expansion.

Barnacles as silent sentinels of microplastic pollution: Evidence from Gujarat coast, India and a global meta-analysis of sessile marine species - Mahima Doshi; Krupal Patel; Jigneshkumar Trivedi (Marine Pollution Bulletin, 2026)

Population Structure and Reproductive Traits of the Porcelain Crab Petrolisthes rufescens (Heller 1861) From Saurashtra Coast, Gujarat State, India - Heris Patel; Krupal Patel; Jigneshkumar N. Trivedi (Marine Ecology, 2026)
The current study examines the population structure and reproductive traits of the porcelain crab Petrolisthes rufescens (Heller 1861) among the samples collected from the rocky intertidal region of Shivrajpur village, located on the Saurashtra coast of Gujarat. Understanding the population ecology of this species is crucial for its significant role in ecological processes, such as nutrient cycling, and its potential susceptibility to environmental stressors. Specimens were collected over 12 consecutive months (March 2019–February 2020) from a 500 m 2 area during low tide using the hand‐picking method. A total of 1191 individuals were collected, comprising 552 males, 475 non‐ovigerous females, and 164 ovigerous females. Adult male individuals were significantly larger than adult non‐ovigerous females, with an average carapace length of 9.28 ± 1.32 mm compared to 8.56 ± 1.12 mm in females. The overall and monthly sex ratios were slightly female‐biased (1:1.2). The size‐frequency distribution in both males and females showed an apparent bimodal pattern. Ovigerous females were present year‐round, suggesting that reproduction occurs on a continuous basis. However, a relatively higher proportion of ovigerous females were observed during March–May and August–October at the Shivrajpur coast over the study period. Reproductive biology was assessed by examining egg characteristics, including total number, size, weight, and alongside the carapace length of ovigerous females. A significant positive correlation was found between the size of ovigerous females and their reproductive output, including total egg count (197 ± 87.53), egg mass weight (10.78 ± 8.26 mg), and egg size (0.59 ± 0.09 mm). This study provides baseline data for future research on the species' response to environmental changes and the increasing anthropogenic pressures affecting coastal ecosystems.

Microplastic ingestion in wild zoanthids: first evidence and a global meta-analysis on cnidarian - Dushyant Joshi; Vasantkumar Rabari; Heris Patel; Jigneshkumar Trivedi (Environmental Monitoring and Assessment, 2025)

Retraction notice to “Microplastic occurrence in commercial crab (Portunus segnis) from the western coast of India and pollution indices: First investigation and evidence” [Sci. Total Environ. 905 (2023) 167500] - Vasantkumar Rabari; Md. Refat Jahan Rakib; Jigneshkumar Trivedi; Abubakr M. Idris; Guilherme Malafaia (Science of The Total Environment, 2024)

Unveiling the population structure and breeding patterns of Petrolisthes boscii (Audouin, 1826) a common intertidal inhabitant of Shivrajpur, Saurashtra Coast, Gujarat - Nayan Patel; Krupal J. Patel; Ashish Patel; Daoud Ali; Saud Alarifi; Jigneshkumar N. Trivedi (Frontiers in Marine Science, 2024)
The present study focused on investigating the population structure and breeding biology of a species of Porcellanid crab, Petrolisthes boscii (Audouin, 1826). Evaluating the population ecology of the species is essential considering its crucial role in ecological functions including the nutrition cycle and its potential vulnerability to environmental stressors. The samples were collected over a period of 12 consecutive months (from March 2019 to February 2020) in an area of 500 m 2 during low tide, utilizing the catch-per-unit-effort (CPUE) method when the water receded. The collected specimens (859 individuals) were categorized into males (407 individuals), non-ovigerous females (452 individuals), and ovigerous females (303 individuals). The assessment of fecundity was conducted by measuring the egg characteristics, including the total number, size, and weight of the eggs, as well as the carapace width of the ovigerous females. There was an evident difference in size, with males (8.60 ± 2.76) being significantly larger compared to females (8.39 ± 2.46) (p < 0.001). The overall and monthly sex ratios were female-biased (1:1.17). Moreover, the size frequency distribution revealed a bimodal distribution in male as well as female individuals. Ovigerous females occurred in all the months, which shows that the species breeds continuously throughout the year, with peaks in the months of March to May and August to October. There was a significant positive relationship observed among the size of ovigerous females and their total number of eggs (130.39 ± 83.31), egg mass weight (150 ± 110 mg). The study may provide baseline information for future studies on the impacts of a continuously altering environment and the consequences of increasing anthropogenic pressure on coastal areas.

The estuarine plastics menace: Insights into prevalence, characterization and polymeric risk assessment of microplastics in the Mahi River Estuary, Gujarat, India - Krunal Pokar; Vasantkumar Rabari; Rishiraj Duggal; Ashish Patel; Heris Patel; Krupal Patel; Virendra Kumar Yadav; Sami Al Obaid; Mohammad Javed Ansari; Jigneshkumar Trivedi (Marine Pollution Bulletin, 2024)

Microplastic contamination in filter-feeding oyster Saccostrea cuccullata: Novel insights in a marine ecosystem - Komal Joshi; Vasantkumar Rabari; Heris Patel; Krupal Patel; Md. Refat Jahan Rakib; Jigneshkumar Trivedi; Bilal Ahamad Paray; Tony R. Walker; Md. Jakariya (Marine Pollution Bulletin, 2024)

Microplastic prevalence in epipelagic layer: Evidence from epipelagic inhabiting prawns of north-west Arabian Sea - Vasantkumar Rabari; Md. Refat Jahan Rakib; Heris Patel; Abubakr M. Idris; Guilherme Malafaia; Jigneshkumar Trivedi (Marine Pollution Bulletin, 2024)

RETRACTED: Microplastics occurrence in commercial crab (Portunus segnis) from the western coast of India and pollution indices: First investigation and evidence - Vasantkumar Rabari; Md. Refat Jahan Rakib; Jigneshkumar Trivedi; Abubakr M. Idris; Guilherme Malafaia (Science of The Total Environment, 2023)

Ingestion and polymeric risk assessment of microplastic contamination in commercially important brachyuran crab Portunus sanguinolentus - Vasantkumar Rabari; Heris Patel; Daoud Ali; Virendra Kumar Yadav; Ashish Patel; Dipak Kumar Sahoo; Jigneshkumar Trivedi (Frontiers in Marine Science, 2023)
Microplastic (MP) in seafood is a growing area of food safety. In the present study, MP contamination in the commercially important crab Portunus sanguinolentus was assessed. A total of 300 crab specimens were collected from three principal fishing harbors of Gujarat. The collected specimens were analyzed for MPs isolation using a previously published protocol. The specimens were dissected, and organs such as the gut and gills were placed separately in the beaker. The organic tissues were digested using 10% KOH. After the digestion, flotation and filtration processes were carried out for the extraction of MPs. The physical (shape, size, and color) and chemical characterization of MPs were performed. The average abundance of MP was recorded as 0.67 ± 0.62 MPs/g. The pollution indices revealed very high contamination and fell under class IV (Jakhau) and V risk categories (Okha and Veraval). Microfibers were found dominantly. Blue and black-colored MPs with 1–2 mm sizes were recorded dominantly. Polyethylene, polyethylene tetraphene, polyurethane, polystyrene, and polypropylene were identified as polymer compositions of MPs. Concludingly, the present study gives an insight into the MP in an important crab species P. sanguinolentus , which can be useful to design further investigations on the toxicity of MPs in seafood.

Population structure and reproductive biology of Clibanarius rhabdodactylus Forest, 1953 (Crustacea: Anomura: Diogenidae) in Gujarat state, India - Krupal J. Patel; Kauresh D. Vachhrajani; Jigneshkumar N. Trivedi (Regional Studies in Marine Science, 2023)

An Assessment of Microplastic Contamination in a Commercially Important Marine Fish, Harpadon nehereus (Hamilton, 1822) - Kalpana Prusty; Vasantkumar Rabari; Krupal Patel; Daoud Ali; Saud Alarifi; Virendra Kumar Yadav; Dipak Kumar Sahoo; Ashish Patel; Jigneshkumar Trivedi (Fishes, 2023)
Microplastic (MP) pollution is a prevalent and global threat to fish. MP contamination was investigated in Harpadon nehereus collected from the principal fishing harbors of India’s northwest coast. A total of 213 specimens were collected from the major fishing harbors of Gujarat state (Jakhau, Okha, and Jaffrabad) and Maharashtra state (Mumbai). In the laboratory, the morphometric parameters of the specimens, such as total length and body weight, were measured. The collected specimens were analyzed for MP isolation using the previously documented protocol. MPs were quantified under a stereomicroscope, and physical parameters were recorded. All the examined specimens were found to be contaminated with MPs, with an abundance of 6.98 ± 6.73 MPs/g. The maximum contamination of MPs was recorded at the study site in Jaffrabad, followed by Jakhau, Mumbai, and Okha. Morphometric analysis of MPs revealed threads to be the most dominant shape. Black and blue MPs with a 1–2 mm size were the predominant recorded types. The chemical composition of extracted MPs revealed polyethylene (PE), polystyrene (PS), and polyurethane (PU) as polymer compositions. Conclusively, the findings highlighted a greater menace to seafood safety due to trophic transfer, which causes a hazardous effect on human health.

Quantitative assessment of microplastic contamination in muddy shores of Gulf of Khambhat, India - Vasantkumar Rabari; Heris Patel; Krupal Patel; Ashish Patel; Snehal Bagtharia; Jigneshkumar Trivedi (Marine Pollution Bulletin, 2023)

First Record of Arcotheres Alcocki (Rathbun, 1909) (Crustacea: Brachyura: Pinnotheridae) from India - Jigneshkumar Trivedi; K. K. Bineesh; Heris Patel (Thalassas: An International Journal of Marine Sciences, 2023)

First Record of Maritigrella fuscopunctata (Prudhoe, 1978) (Polycladida: Cotylea: Euryleptidae) from the Coastal area of Mainland India - Heris Patel; Krupal Patel; Jigneshkumar Trivedi (Thalassas: An International Journal of Marine Sciences, 2023)

Study on Shell Utilization Pattern of Two Sympatric Hermit Crab Species on the Rocky Intertidal Region of Veraval, Gujarat, India - Krupal J. Patel; Kauresh D. Vachhrajani; Jigneshkumar N. Trivedi (Thalassas: An International Journal of Marine Sciences, 2023)

Diversity of Indian Barnacles in Marine Provinces and Ecoregions of the Indian Ocean - Jigneshkumar Trivedi; Krupal Patel; Benny K. K. Chan; Mahima Doshi; Vinay Padate (Frontiers in Marine Science, 2021)
The present study is the first completed and taxonomically validated literature review of the biodiversity of barnacles (Cirripedia) in India. A total of 144 species in 75 genera and 19 families have been recorded in India. The highest number of species has been recorded from the Bay of Bengal province, located on the eastern side of the Indian Peninsula, comprising the Eastern India ecoregion (76 species) and Northern Bay of Bengal ecoregion (34 species). The West and South India Shelf province has fewer species (Western India ecoregion: 29 species; South India and Sri Lanka ecoregion: 40 species; and Maldives ecoregion: 10 species) compared to the Bay of Bengal province. The Andaman province is composed of the Andaman and Nicobar Islands, and contains 65 species. Most of the coral-associated barnacles (family Pyrgomatidae) have been recorded in the corals reefs of the Andaman and Nicobar Islands (7 species), Eastern India (6 species), and Northern Bay of Bengal ecoregions (5 species). Sponge-associated barnacles (mostly in the subfamily Acastinae) were recorded in the Eastern India ecoregion, Southern India and Sri Lanka, and Andaman and Nicobar Islands ecoregions. Deepwater species were recorded the most extensively in the Andaman and Nicobar Islands ecoregion (21 species), followed by the South India and Sri Lanka ecoregion (9 species) and Eastern India ecoregion (7 species). Six Atlantic/boreal cold water species previously reported in India were removed due to incorrect identification, and some incorrectly identified species were validated and corrected.

Four New Records of Brachyuran Crabs (Crustacea: Decapoda: Brachyura) from India - Jigneshkumar Trivedi; Santanu Mitra; Pooja Patel; Swapnil Gosavi; Kauresh Vachhrajani (Thalassas: An International Journal of Marine Sciences, 2021)

Range Extension of Two Brachyuran Crabs (Crustacea: Decapoda), Acanthonyx inglei Tirmizi & Kazmi, 1988 (Epialtidae) and Scalopidia indica Ng & Castro, 2013 (Scalopidiidae) in India - Jigneshkumar Trivedi; Swapnil Gosavi; Kauresh Vachhrajani (Thalassas: An International Journal of Marine Sciences, 2018)